The Current Status of Direct Oral Anticoagulants in Cancer-Related Venous Thromboembolism Treatment - К. V. Lobastov; I. V. Schastlivtsev (Рациональная фармакотерапия в кардиологии, 2020)
This article is a review of epidemiology, pathogenesis and treatment of venous thromboembolism (VTE) in cancer patients. In accordance with actual guidelines, the duration of anticoagulant therapy of cancer-related venous thrombosis should be at least 6 months. The use of vitamin K antagonists (VKA) is associated with an increased risk of VTE recurrence and bleeding, so low molecular weight heparin (LMWH), in particular dalteparin, has been the "gold standard" until recently. Compared to VKA, prolonged use of LMWH can reduce the incidence of VTE recurrence without affecting the risk of bleeding or death. The main disadvantage of LMWH is low compliance, leading to premature discontinuation of treatment or switching to alternative anticoagulants. Direct oral anticoagulants (DOACs) have changed the situation. Compared to VKA, they demonstrated higher efficacy with a similar (or improved for individual DOACs) safety in patients with cancer-related VTE. Recently, the results of studies comparing the use of DOACs with dalteparin in cancer patients have been published: SELECT-D (rivaroxaban), HOKUSAI-VTE Cancer (edoxaban), ADAM VTE (apixaban), CARAVAGGIO (apixaban). Rivaroxaban showed higher efficacy than dalteparin with a similar risk of major bleeding, but an increased risk of clinically relevant non-major (CRNM) bleeding. Edoxaban had the same efficacy as dalteparin but increased risk of major but not CRNM bleeding. Apixaban showed similar efficacy and safety as dalteparin in the CARAVAGGIO study, but did not provide higher safety in the ADAM VTE study. It was noted that gastrointestinal and urogenital bleeding dominated in the structure of hemorrhagic complications of DOACs. The results of published trials are reflected in the current guidelines of the specialized societies. DOACs (particularly, rivaroxaban and edoxaban) are recommended for the VTE treatment in cancer patients.